2019
DOI: 10.1186/s13104-019-4235-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of ultrasound characteristics in the identification of malignant thyroid nodules

Abstract: Objective This study was aimed at determining the diagnostic accuracy of the ultrasound characteristics in the identification of malignant thyroid nodules in patients attending the surgical clinic at a tertiary care hospital in Sri Lanka. Results This prospective validation study was conducted among 263 patients attending the surgical clinic at a tertiary care hospital, Sri Lanka. The ultrasound characteristics having statistically significant associations with thyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
5
12
0
Order By: Relevance
“…In this study, five typical ultrasound characteristics were analyzed as predictor of thyroid malignancy. It was congruent with the findings of most previous studies (Moon et al, 2008;Wettasinghe et al, 2019;Alam et al, 2014). ECHO nodules showed a sensitivity of 87.1% in another study conducted on 500 patients (Papini et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, five typical ultrasound characteristics were analyzed as predictor of thyroid malignancy. It was congruent with the findings of most previous studies (Moon et al, 2008;Wettasinghe et al, 2019;Alam et al, 2014). ECHO nodules showed a sensitivity of 87.1% in another study conducted on 500 patients (Papini et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…It suggested that the nodule size has a limit effect on OR values of TTW. Previous studies suggested that EF and ITC are reliable indicators of diagnostic accuracy(Wettasinghe et al, 2019) (Nachiappan et al, 2014). Our results showed that both EF and ITC have biggest OR values in nodules with size >1 cm.…”
supporting
confidence: 61%
“…Therefore, scintigraphy findings should be confirmed by ultrasound to avoid false positive results [18]. Ultrasonography is a better diagnostic tool as it is widely available and costeffective with no radiation exposure to the patient [19]. However, in case of ectopic thyroid gland in the retrosternal or mediastinal location, scintigraphy with I-123 is the investigation of choice as it has high specificity [20].…”
Section: Discussionmentioning
confidence: 99%
“…This tool will help the radiologist to further guide for the need of FNAC on selected patients as it is not possible to target all the nodules to aspiration which can be both a financial and physical burden. 9 So, nodules classified into U2 were always benign so they just needed to be reported as such, no intervention was needed. But categories U4 and U5 had features which either in solitude or multitude were associated with malignancy, so had to be aspirated.…”
Section: Discussionmentioning
confidence: 99%